Implementation of Dietary Supplements with Effect of Dezintoxication and Improvement of Osteogenesis and Metabolism - Volodina, T.T.; Korotkevich, N.V.; Romaniuk, S.I.; Galkin, O.Yu.; Kolybo, D.V.; Komisarenko, S.V. (Science and Innovation, 2024)
Bone diseases are quite common among the Ukrainian population and occur in most children with leukemia. Therefore, the Corectin preparation has been developed on the basis of fundamental research conducted earlier at the Palladin Institute of Biochemistry of the NAS of Ukraine. Corectin has proved itself to be an effective remedy for the treatment of bone lesions of various genesis, including those occurring in hemoblastoses. The purpose of this research is to assess the prospects for application of Corectin and Glycivit C dietary supplements based on Corectin preparation and to introduce them into production. As a result, it has shown that these dietary supplements can be used as an additional source of glycine for functional normalization of nervous and immune systems. It increases bone density, cleanses the blood, decreases psycho-emotional tension, speeds up alcoholic detoxification, and, possibly, can be used for the treatment of bone and liver diseases and oncohematological pathologies. The obtained results of marketing research testify that bringing the developed supplements to market will be expedient. The trial batches of dietary supplements have been made with involvement of Nutrimed LTD (Ukraine). The specifications for production have been approved and listed in the national registry of specifications. The developed supplements have been endorsed by State Research Center for Food Hygiene of the Ministry of Health of Ukraine and the Marzeev Institute of Public Health of NAMS of Ukraine.